Організація обліку та внутрішнього контролю в дошкільних навчальних закладах в умовах централізованої бухгалтерії - Ткаліч, Вікторія Володимирівна; Tkalich, Viktoriia (ЦНТУ, 2024)
В першому розділі досліджено теоретичні засади організації обліку і внутрішнього контролю в умовах запровадження централізованої бухгалтерії, розкрито сутність дошкільних навчальних закладів, проаналізовано кількісні показники розвитку закладів дошкільної освіти в Україні за останні роки, досліджено форми організації обліку та особливості регламентації централізованої бухгалтерії, визначені мета, задачі та функції обліку і внутрішнього контролю в дошкільних навчальних закладах. В другому розділі проаналізовано основні показники діяльності дошкільного навчального закладу, його структуру, функції органів управління, висвітлено основні правила організації обліку та внутрішнього контролю в дошкільному навчальному закладі та його взаємодію із централізованою бухгалтерією та вплив централізованої бухгалтерії. В третьому розділі визначені шляхи розвитку обліку в умовах функціонування централізованої бухгалтерії, узагальнено фактори, які впливають на прийняття рішення щодо вибору форми ведення обліку в дошкільних навчальних закладах, запропоновано основні напрями розвитку внутрішнього контролю в дошкільних навчальних закладах. In the first chapter, the theoretical principles of the organization of accounting and internal control in the conditions of the introduction of centralized accounting were investigated, the essence of preschool educational institutions was revealed, the quantitative indicators of the development of preschool education institutions in Ukraine in recent years were analyzed, the forms of accounting organization and the peculiarities of the regulation of centralized accounting were investigated, the purpose, tasks and functions of accounting and internal control in preschool educational institutions were determined. In the second section, the main indicators of the activity of the preschool educational institution, its structure, functions of management bodies are analyzed, the main rules for the organization of accounting and internal control in the preschool educational institution and its interaction with centralized accounting and the influence of centralized accounting are highlighted. In the third section, the ways of development of accounting in the conditions of the functioning of centralized accounting are determined, the factors influencing the decision-making regarding the choice of the form of accounting in preschool educational institutions are summarized, the main directions of the development of internal control in preschool educational institutions are proposed.
Organization of accounting and internal control in preschool educational institutions in the conditions of centralized accounting
Keywords: дошкільні навчальні заклади; облік; внутрішній контроль; централізована бухгалтерія; форми організації обліку; нормативне регламентування; субєкти внутрішнього контролю; preschool educational institutions; accounting; internal control; centralized accounting; forms of accounting organization; normative regulation; subjects of internal control